2020
DOI: 10.1038/s41598-020-60620-3
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem volume mediates seasonal variation in depressive symptoms: A cross sectional study in the UK Biobank cohort

Abstract: Seasonal differences in mood and depressive symptoms affect a large percentage of the general population, with seasonal affective disorder (SAD) representing the most common presentation. SAD affects up to 3% of the world's population, and it tends to be more predominant in females than males. The brainstem has been shown to be affected by photoperiodic changes, and that longer photoperiods are associated with higher neuronal density and decreased depressive-like behaviours. We predict that longer photoperiod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…The VTA is not the only non-hypothalamic region recently uncovered for its rhythmic role in emotion. In schizophrenia, which is characterized by psychotic behaviors, transcript analysis in post-mortem brain tissues schizophrenia patients reveal altered rhythmic gene expression in the dorsolateral prefrontal cortex [ 330 ]. The hypothalamic region is still likely involved in schizophrenia as other studies have found increases in hypothalamic volume [ 350 ] and attenuated AVP mRNA expression in the hypothalamus [ 351 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Neuromentioning
confidence: 99%
“…The VTA is not the only non-hypothalamic region recently uncovered for its rhythmic role in emotion. In schizophrenia, which is characterized by psychotic behaviors, transcript analysis in post-mortem brain tissues schizophrenia patients reveal altered rhythmic gene expression in the dorsolateral prefrontal cortex [ 330 ]. The hypothalamic region is still likely involved in schizophrenia as other studies have found increases in hypothalamic volume [ 350 ] and attenuated AVP mRNA expression in the hypothalamus [ 351 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Neuromentioning
confidence: 99%
“…Majrashi и соавт. [18] обнаружена отрицательная корреляция длины светового периода с плохим настроением и ангедонией у женщин. У мужчин не наблюдалось никаких опосредованных эффектов.…”
Section: Discussionunclassified
“…There is evidence showing the impact of changes in environmental factors such as photoperiod on brain morphology. Recent previous studies (Majrashi, Ahearn, & Waiter, 2020; Majrashi, Ahearn, Williams, & Waiter, 2020; Miller et al, 2015) have found that photoperiod (day length) is positively associated with the volume of brain regions such as the hippocampus and brainstem substructures and that individuals exposed to longer photoperiod days exhibited larger hippocampal and brainstem substructure volumes compared with those exposed to shorter photoperiod days. The amygdala, a region responsible for emotion, cognition and social behaviours (Pessoa, 2010), has also been shown to be affected by seasonal differences in photoperiod in animals (Romeo & Sisk, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…In humans, seasonal morphological differences in brain volume, particularly the brainstem, have been implicated in seasonal depressive symptoms. Brainstem volume was found to mediate the relationship between seasonal differences in photoperiod and depressive symptoms, including low mood and anhedonia, in females but not in males (Majrashi, Ahearn, & Waiter, 2020). In light of the importance of the amygdala to mood regulation and the lack of research linking seasonal variations in photoperiod to seasonal variations in mood and amygdala volume, the aims of this study were to (a) test the seasonal pattern of amygdala and subregion volumes; (b) explore whether photoperiod is associated with amygdala and subregion volume, as well as depressive symptoms; and if so, (c) explore whether the effect of photoperiod on mood might be mediated by seasonal variations in amygdala morphology.…”
Section: Introductionmentioning
confidence: 99%